Editorial - Chacón Alvarado, Lucía (2003)
Advances in communication technology and information have reshaped human scenarios and how to run the world. The processes are simple, immediate and global, but merit of knowledge, skills and technologies.A few decades ago, when Bush came up with the ME Vannaver MEX, it was difficult to conceptualize, that almost unlimited access between two international military points. Later, Jorge Luis Borges dreamed Global Library, to which is entered through doors and hexagonal which flows the universal knowledge. All these events, which are facts today, tales of goblins and would be heresy to the monks who guarded the libraries in the Middle Ages. I imagine the immediate access to ancient and modern collections of other libraries and other countries from a single income?.